Development of Interactive Teaching Materials on Google Sites using a Problem-Based Learning Model for Fifth-Grade Indonesian Language Instruction - Meri Yani; Desyandri Desyandri; Adrias Adrias; Ulfia Rahmi (FKIP - Universitas Riau, 2026)
This study aimed to develop interactive teaching materials assisted by Google Sites using a Problem Based Learning (PBL) model for fifth-grade Indonesian language instruction. Interactive teaching materials are defined as digital learning resources designed to actively engage students through interaction with content, tasks, and problem-solving activities, enabling meaningful cognitive involvement during learning. This research was conducted due to the limited use of interactive digital teaching materials in elementary schools, which often results in low student engagement. The study employed a Research and Development approach using the ADDIE instructional design process, including analysis, design, development, implementation, and evaluation stages. Data were collected through observations, interviews, expert validation sheets, practicality questionnaires, and pre-test and post-test instruments in three elementary schools. The validation results showed a validity coefficient of 0.905, categorized as highly valid. Practicality testing indicated very high practicality, with teacher and student responses of 99.58% and 94.16%, respectively. Effectiveness testing demonstrated high effectiveness, with an N-Gain score of 0.80 (80.55%). These findings indicate that Google Sites–assisted interactive teaching materials integrated with the PBL model are valid, practical, and effective for improving student engagement and learning outcomes in elementary Indonesian language learning.